PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP NIAT PEMBELIAN ULANG DENGAN KEPUASAN PELANGGAN SEBAGAI VARIABEL INTERVENING PELANGGAN PRODUK CONVERSE - Ganung Pradita; Irmawati (MANAJEMEN DEWANTARA, 2024)
The population in Indonesia is very dense and large, which is a very promising or potential market for companies to market the products created by these companies. With so many different product choices and types of products on the market, consumers will first choose according to their needs by considering quality and price, as well as the satisfaction they receive. The subject of this research was Converse products, data was obtained from 135 consumers collected through questionnaires. Meanwhile, the objects are product quality, product price and consumer satisfaction. This data will be analyzed using Structural Equation Model (SEM) analysis with Partial Least Square (PLS). Based on the results of the analysis, it was found that product quality and price had a positive and significant impact on satisfaction and intention to repurchase Converse. Apart from that, satisfaction is also able to mediate the influence of product quality and price on repurchase intentions